High Glucose Concentration Impairs 5-PAHSA Activity by Inhibiting AMP-Activated Protein Kinase Activation and Promoting Nuclear Factor-Kappa-B-Mediated Inflammation - Wang, Yan-Mei; Liu, Hong-Xia; Fang, Ning-Yuan (Frontiers in Pharmacology, 2019)
Recently, the endogenous fatty acid palmitic acid-5-hydroxystearic acid (5-PAHSA) was found to increase insulin sensitivity and have anti-inflammatory effects in mice with high-fat diet (HFD)-induced diabetes. However, it is unknown if 5-PAHSA affects glucose and lipid metabolism in db/db mice, which are characterized by extreme hyperglycemia. Here, we aim to determine the effect of continued 5-PAHSA administration on glucose and lipid metabolism in db/db mice. We also used 3T3-L1 cells and HepG2 cells to investigate the mechanism behind this effect. HepG2 cells and 3T3-L1 cells were induced to become models of insulin resistance. The models were used to test the effect of 5-PAHSA on insulin signaling. 5-PAHSA was administered orally to db/db mice for 1 month to assess its effects on glucose and lipid metabolism. We also exposed HepG2 cells to high glucose concentrations to investigate the influence on 5-PAHSA’s effects on hepatic lipid metabolism and inflammation. 5-PAHSA improved glucose uptake and insulin signaling in HepG2 cells and 3T3-L1 cells. However, after 1 month of treatment, 5-PAHSA did not reduce blood glucose levels, but increased inflammation and promoted fatty liver in db/db mice. In HepG2 cells under normal glucose conditions, 5-PAHSA treatment reduced lipogenesis and increased lipid oxidation. Notably, a high glucose concentration in cell media abolished the positive effects of 5-PAHSA treatment. These changes were associated with: decreased phosphorylation of AMP-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC); upregulation of sterol-regulatory element-binding protein 1c (SREBP1c), and fatty acid synthase (FAS); and downregulation of carnitine palmitoyltransferase 1 (CPT1). Besides, the anti-inflammatory effect of 5-PAHSA was also impaired by high glucose conditions. Thus, high glucose concentrations impaired 5-PAHSA action by inhibiting the AMPK signaling pathway and promoting nuclear factor-kappa-B (NF-κB) mediated inflammation.